Comparative performance evaluation of routing algorithm and topology size for wireless network-on-chip - Asrani Lit; M. S. Rusli; M. N. Marsono (Bulletin of Electrical Engineering and Informatics, 2019)
Wireless Network-on-Chip or WiNoC is an alternative to traditional planar on-chip networks. On-chip wireless links are utilized to reduce latency between distant nodes due to its capability to communicate with far-away node within a single hop. This paper analyzes the impact of various routing schemes and the effect of WiNoC sizes on network traffic distributions compared to conventional mesh NoC. Radio hubs (4×4) are evenly placed on WiNoC to analyze global average delay, throughput, energy consumption and wireless utilization. For validation, three various network sizes (8×8,   16×16 and 32×32) of mesh NoC and WiNoC architectures are simulated on cycle-accurate Noxim simulator under numerous traffic load distributions. Simulation results show that WiNoC architecture with the 16×16 network size has better average speedup (∼1.2×) and improved network throughputs by 6.36% in non-uniform transpose traffic distribution. As the trade-off, WiNoC requires 63% higher energy consumption compared to the classical wired NoC mesh.